2002
DOI: 10.1111/j.1749-6632.2002.tb04497.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasostatins Exert Negative Inotropism in the Working Heart of the Frog

Abstract: An in vitro isolated working frog heart (Rana esculenta) was used to study the effects of exogenous CGA(1-76) (vasostatin 1), CGA(1-113) (vasostatin 2), and the synthetic CGA(7-57) on cardiac performance. Under basal cardiac conditions, the dose-response curves of the three peptides from 10(-8) to 10(-7) M showed a significant calcium-dependent negative inotropism that involved neither the endocardial endothelium nor the adrenergic and muscarinic receptors. In addition, the CgA fragments clearly counteracted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…Therefore, it has been suggested that VSs, in addition to their vasoinhibitory properties, are cardioregulatory mediators; i.e., they are able to exert an antiadrenergic action that could protect the heart against intense excitatory stimulations, such as those elicited by the stress response (9,11,19,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has been suggested that VSs, in addition to their vasoinhibitory properties, are cardioregulatory mediators; i.e., they are able to exert an antiadrenergic action that could protect the heart against intense excitatory stimulations, such as those elicited by the stress response (9,11,19,26).…”
Section: Discussionmentioning
confidence: 99%
“…The negative inotropism exerted by VS-1, even with different mechanisms, has been observed in several vertebrate species. VS-1 and VS-2 induce a negative inotropic effect on the isolated heart of the eel (19), frog (11,12,26), and rat (9) under basal conditions and after ␤-adrenergic stimulation. Interestingly, although the action of VSs on frog cardiac muscle appears direct, i.e., independent of endocardial endothelial (EE) cells and muscarinic/␤-adrenergic-related pathways (12,26), in the heart of the eel, it depends on EE-dependent activation of M 1 muscarinic receptors and G i/o , as well as synthesis of nitric oxide (NO) and cGMP (19).…”
mentioning
confidence: 99%
“…The first experimental models were isolated segments of human intrathoracic arteries and saphenous veins (Aardal and Helle 1992;Aardal et al 1993;Angeletti et al 1994), revealing suppressive effects on precontracted vessel segments. Most recently, several models of the vertebrate heart have been introduced (Corti et al 2002;Imbrogno et al 2004;Cerra et al 2006). Common to the vertebrate hearts is a negative myocardial inotropy elicited not only by the highly conserved VS-I domain in CgA but also by CAT.…”
Section: Other Cardiovascular Functionsmentioning
confidence: 98%
“…Contrary to earlier assumptions, CgA is not only a product of neuronal and glandular elements of the neuroendocrine system but appear also as a product of cardiocytes and polymorphonuclear neutrophils (PMNs). Accordingly, vertebrate hearts have proved fruitful as models for functional effects of not only VS-I (Corti et al 2002(Corti et al , 2004Tota et al 2003;Imbrogno et al 2004;Cerra et al 2006Cerra et al , 2008Cappello et al 2007;Gallo et al 2007) but also of CAT (Mazza et al 2008;Angelone et al 2008).…”
Section: Cgamentioning
confidence: 99%
“…CGA is a prohormone precursor and is proteolysed by proteases via numerous cleavage sites [64] in a tissue-specific manner [65], resulting in the formation of catestatin and vasostatins, which exert a autocrine/paracrine negative feedback control on local catecholamine release [66] and vascular dilation [67]. Vasostatins exert a negative inotropic effect on isolated frog and eel hearts and counteract the actions of -adrenergic drugs [68,69]. BNP and CGA are co-stored in the myocardium of patients with dilated cardiomyopathy, whereas this co-localisation was not found in healthy controls [70].…”
Section: Natriuretic Peptides and Chromogranin Amentioning
confidence: 99%